Rekayasa Perangkat Lunak Sistem Informasi Kehadiran Dosen Berbasis SMS GATEWAY (Studi Kasus: STMIK Logika Medan) - Subhan Hafiz Nanda Ginting; Dewi Wahyuni (Jurnal Multimedia dan Teknologi Informasi (Jatilima), 2022)
Information that reaches students is frequently unclear because there isn't a structure in place to quickly and accurately inform students of the presence of lecturers. Therefore, it is essential to develop an information system that can accurately and swiftly communicate the presence of lecturers. The information system that the author offers is an SMS getaway-based information system that can assist in informing pupils. The information system developed is intended to increase the quality of the information provided to students by STMIK LOGIKA and to make it simpler for students to learn about the presence of lecturers.